Sex modifies the association between HIV and coronary artery disease among older adults in Uganda. Issue 1 (7th January 2022) - Longenecker, Chris T.; Bogorodskaya, Milana; Margevicius, Seunghee; Nazzinda, Rashidah; Bittencourt, Marcio Sommer; Erem, Geoffrey; Nalukwago, Sophie; Huaman, Moises A.; Ghoshhajra, Brian B.; Siedner, Mark J.; Juchnowski, Steven M.; Zidar, David A.; et al.
Abstract: Introduction: Little is known about the epidemiology of coronary artery disease (CAD) in sub‐Saharan Africa, where the majority of people living with HIV (PLHIV) live. We assessed the association of HIV with CAD and explored relationships with monocyte activation in sex‐stratified analyses of older PLHIV and people without HIV (PWOH) in Uganda. Methods: The Ugandan Study of HIV effects on the Myocardium and Atherosclerosis (mUTIMA) follows 100 PLHIV on antiretroviral therapy (ART) and 100 age‐ and sex‐matched PWOH controls in Kampala, Uganda; all >45 years of age with >1 cardiovascular disease risk factor. At the year 2 exam (2017–2019), 189 participants had available coronary calcium score and 165 had coronary CT angiography (CCTA) for this analysis. A subset of participants ( n = 107) had both CCTA and fresh whole blood flow cytometry for monocyte phenotyping. Results: Median age was 57.8 years and 63% were females. Overall, 88% had hypertension, 37% had diabetes and 4% were smokers. Atherosclerotic cardiovascular disease (ASCVD) risk was modestly higher for PWOH, but not statistically significant (median 10‐year ASCVD risk 7.2% for PLHIV vs. 8.6% for PWOH, p = 0.09). Median duration of ART was 12.7 years and 86% had suppressed viral load. Despite a high prevalence of risk factors, only 34/165 (21%, 95% CI 15–28%) had any coronary plaque. After adjustment for ASCVD risk score, HIV status was not associated with CAD (OR 0.55, 95% CI 0.23–1.30) but was associated with more severe CAD (segment severity score>3) among those with disease (OR 10.9, 95% CI 1.67–70.45). Females had a trend towards higher odds of CAD among PLHIV (OR 4.1, 95% CI 0.4–44.9), but a trend towards lower odds of CAD among PWOH (OR 0.30; 95% CI 0.07–1.3; HIV*sex interaction p = 0.019). CAD was positively correlated with classical monocytes ( r = 0.3, p = 0.012) and negatively correlated with CX3CR1 expression ( r = –0.31, p = 0.011) in PLHIV and negatively correlated with patrolling monocytes ( r = –0.36, p = 0.031) and tissue factor expression ( r = –0.39, p = 0.017) in PWOH. Conclusions: Our results suggest that HIV may be associated more with severity rather than the presence of CAD in Uganda. Sex differences in the HIV effect suggest that tailored CAD prevention strategies may be required in this setting.